Diverse Physiological Functions of FAB1 and Phosphatidylinositol 3,5-Bisphosphate in Plants - Hirano, Tomoko; Sato, Masa H. (Frontiers in Plant Science, 2019)
Biological membranes are predominantly composed of structural glycerophospholipids such as phosphatidylcholine, phosphatidylethanolamine, and phosphatidylinositol. Of the membrane glycerophospholipids, phosphatidylinositol (PtdIns) and its phosphorylated derivatives (phosphoinositides) constitute a minor fraction that exert a wide variety of regulatory functions in eukaryotic cells. Phosphoinositides, which comprise 3 PtdIns monophosphates, 2 PtdIns bisphosphates, and one PtdIns triphosphate, phosphorylate the hydroxy groups of the inositol head group of phosphatidylinositol by specific lipid kinases. Among the total phosphoinositides available in a cell, phosphatidylinositol 3,5-bisphosphate [PtdIns(3,5)P2] constitutes the smallest fraction; however, it is a crucial lipid in the animal and yeast membrane trafficking systems. In this review, we focus on the recent findings on the physiological functions of PtdIns(3,5)P2 and its catalyst enzyme—formation of aploid and binucleate cells (FAB1) —along with the regulatory proteins of FAB1 and the downstream effector proteins of PtdIns(3,5)P2 in Arabidopsis.